Surface-engineered Oxidized Two-dimensional Sb for Efficient Visible Light-Driven N2 Fixation - Zhao, Zhenqing; Choi, Changhyeok; Hong, Song; Masa, Justus; Jung, Yousung (Nano Energy, 2020)
Solar N2 fixation under visible light offers a promising method toward sustainable NH3 production at benign conditions. However, it still remains a formidable challenge to activate and cleave Ntriple bondN bonds and promote the separation and transport of electrons and holes during photocatalysis. To address these issues, the discovery and design of high-performance and robust photocatalysts is imperative. Here, we report the defect engineering of two-dimensional oxidized Sb nanosheets to activate intrinsically inactive Sb for efficient visible light-driven N2 reduction to NH3. Impressively, the Sb nanosheets rich in Sb and oxygen vacancies afford a remarkable NH3 formation rate of up to 388.5 μgNH3 h−1 gcat.−1 without cocatalyst in visible light, 8 times higher than that for bulk Sb and also significantly outperforming many previously reported photocatalysts. The defective Sb nanosheets exhibit excellent stability after five successive reaction cycles. Further density functional theory calculations reveal a considerably strong interaction between N2 and defects on the surface and edge of Sb nanosheets, which facilitates the formation of *NNH (N2 + (H+ + e-) → *NNH, where * denotes an adsorption site), thus promoting photocatalytic N2 reduction. This finding opens a novel avenue to enhancing N2 photofixation over inherently inactive surfaces by synergistically engineering defect sites.
Keywords: N2 fixation; Photocatalysis; Two-dimensional Sb; Visible light; Vacancy